VARS2 depletion leads to activation of the integrated stress response and disruptions in mitochondrial fatty acid oxidation - Kayvanpour, Elham; Wisdom, Michael; Lackner, Maximilian K.; Sedaghat-Hamedani, Farbod; Boeckel, Jes-Niels; Müller, Marion; Eghbalian, Rose; Dudek, Jan; Doroudgar, Shirin; Maack, Christoph; Frey, Norbert; Meder, Benjamin (International journal of molecular sciences, 2022)
Mutations in mitochondrial aminoacyl-tRNA synthetases (mtARSs) have been reported in patients with mitochondriopathies: most commonly encephalopathy, but also cardiomyopathy. Through a GWAS, we showed possible associations between mitochondrial valyl-tRNA synthetase (VARS2) dysregulations and non-ischemic cardiomyopathy. We aimed to investigate the possible consequences of VARS2 depletion in zebrafish and cultured HEK293A cells. Transient VARS2 loss-of-function was induced in zebrafish embryos using Morpholinos. The enzymatic activity of VARS2 was measured in VARS2-depleted cells via northern blot. Heterozygous VARS2 knockout was established in HEK293A cells using CRISPR/Cas9 technology. BN-PAGE and SDS-PAGE were used to investigate electron transport chain (ETC) complexes, and the oxygen consumption rate and extracellular acidification rate were measured using a Seahorse XFe96 Analyzer. The activation of the integrated stress response (ISR) and possible disruptions in mitochondrial fatty acid oxidation (FAO) were explored using RT-qPCR and western blot. Zebrafish embryos with transient VARS2 loss-of-function showed features of heart failure as well as indications of CNS and skeletal muscle involvements. The enzymatic activity of VARS2 was significantly reduced in VARS2-depleted cells. Heterozygous VARS2-knockout cells showed a rearrangement of ETC complexes in favor of complexes III2, III2 + IV, and supercomplexes without significant respiratory chain deficiencies. These cells also showed the enhanced activation of the ISR, as indicated by increased eIF-2α phosphorylation and a significant increase in the transcript levels of ATF4, ATF5, and DDIT3 (CHOP), as well as disruptions in FAO. The activation of the ISR and disruptions in mitochondrial FAO may underlie the adaptive changes in VARS2-depleted cells.
Gesehen am 07.11.2024